Reply to "Do genome‐scale models need exact solvers or clearer standards?". Issue 10 (14th October 2015) - Chindelevitch, Leonid; Trigg, Jason; Regev, Aviv; Berger, Bonnie
Abstract : Chindelevitch et al address the issues raised by Ebrahim et al and advocate that both improved standards and exact arithmetic are needed to advance the field.